ASYMMETRIC DIELS-ALDER REACTIONS OF A NITROSO COMPOUND DERIVED FROM D-BORNANE-10,2-SULTAM - Gouverneur, V; Dive, G; Ghosez, L (1991)
Acylnitroso dienophile 3 derived from D-bornane-10,2-sultam undergoes cycloaddition with high yields and complete facial selectivity to cyclopentadiene and cyclohexadiene. When the nitroso group is attached to the sultam nitrogen, it is no longer reactive in Diels-Alder reactions. © 1991.